Dinâmica da inovação tecnológica no Brasil: estudo do segmento de máquinas e implementos agrícolas - Lucente, Adriano dos Reis (2010)
This study aimed to characterize the dynamics of technological innovation in Brazilian MIA segment. To achieve this objective this work realized a survey with IBGE information, the institution responsible for carrying out PINTECs occurred between 1998 and 2005, which allowed a quantitative analysis about technological innovations on MIA companies. In addition, a national scenario with a qualitative analysis was elaborated, based on surveys conducted by IBGE and on a field research in five MIA´s manufacturers companies of São Paulo state. Results indicate that technological changes have changed the way MIA companies treat the needs of their customers by improving the processes of development and manufacture of products. Moreover, it was found that the variables size and export orientation significantly influence the innovative activities. The influence of size company on innovative activity is justified by the fact that the larger companies find it easier to finance innovative projects and the returns of innovation are more expressive when the company has increased sales volume and the fixed costs are more easily absorbed. The export orientation also generates positive impacts on the ability to innovate, because the international competitiveness encourages investments in innovative activities. Exports, while facilitating the expansion of markets, contributing effectively to the reduction of fixed costs generated in the process of innovation.